CHARACTERISTICS OF AGING OF WOOD-FIBERBOARD FROM THE POSITION OF IR SPECTROSCOPY - Bulgakov, Alexey Grigoryevich; Semyon, Mamontov; Alexander, Mamontov; Yuri Leonidovich, Rapatsky (Journal of Applied Engineering Science, 2020)
Fiber boards, like other wood-polymer composites, are widely used in construction. However, their service life is often less than that declared by the manufacturer, which is due to insufficient knowledge of the processes of degradation of polymer components of resin and wood filler under the influence of aggressive environmental factors. In this regard, the task is to reveal, using reflective IR spectroscopy, structural changes in the molecular structure of polymeric substances included in a wood fiber composite after heat aging, artificial UV radiation and exposure to direct sunlight. The results of the study showed that the IR spectra of all samples are identical, but differ in the intensity of individual absorption bands. This suggests that under the influence of aging factors, a free-radical rupture of hydrogen, hydrocarbon and ether bonds occurs in various functional groups of cellulose, hemicellulose, lignin and resin. At the same time, heat aging causes structural changes throughout the entire volume of the slab, and artificial UV irradiation destroys the surface layer about one millimeter thick. Sunlight during the summer season destroys the surface layer less than 0.5 mm thick and contributes to additional structuring of the polymer components of the resin and wood of the inner layers as a result of heating the board.
Keywords: fibreboards; heat aging; UV irradiation; IR spectroscopy